직무발명보상에서 조직의 공정성이 조직유효성에 미치는 영향에 관한 연구 - 김운선; Kim Woonsun; 이승배; Lee Seungbae; 유왕진; Yoo Wangjin (지식재산연구, 2018)
본 연구는 사용자가 종업원의 직무발명에 대한 양도대가로 지급하는 직무발명보상에 있어서 조직의 공정성이 조직유효성에 영향을 미치고 있음을 실증 분석을 통해 검정하였다. 본 연구를 위해 직무발명보상을 모범적으로 실시하여 직무발명보상 우수기업으로 인증받은 중소벤처기업 119개사를 연구 대상으로 하여 실증분석을 실시하였다. 실증분석을 위해 연구모형 설계와 연구가설을 설정하고 다중회귀분석을 실시하였다. 분석결과, 첫째, 직무발명보상에 있어서 절차 공정성, 분배 공정성, 상호작용 공정성이 종업원의 직무만족에 모두 정(+)의 영향을 미치는 것으로 나타났다. 둘째, 직무발명보상에 있어서 상호작용 공정성이 조직몰입에 정(+)의 영향을 미치는 것으로 나타났으며, 셋째, 분배 공정성, 상호작용 공정성이 조직발전에 공헌하려는 종업원의 자발적 행동을 유발하는 조직시민행동에 정(+)의 영향을 미치는 것으로 나타났다. 본 연구는 다음과 같이 몇 가지 의미 있는 시사점을 제공하고 있다. 첫째, 직무발명보상을 시행함에 있어 ‘정당한 보상’뿐만 아니라 ‘공정한 보상’이 되어야 함을 입증하였다. 종업원이 열심히 일한 만큼 보상을 받는다는 인식을 통해 종업원의 발명의욕을 고취시켜 우수한 발명을 창출하기 위해서는 정당하면서 공정한 직무발명보상이 되어야 할 것이다. 둘째, 종업원이 조직과 자신의 직무에 공헌하고 기여하려는 자발적 행동을 유발시키기 위해서는 직무발명보상수준이 종업원의 기대심리에 충족하도록 ‘상당한 보상’이 되어야 할 것이다. This study empirically analyzed the effect of organizational justice and organizational effectiveness on employee invention compensation paid by employer in exchange for employee invention. This study used a sample of 119 SMEs and venture firms certified as excellent employee invention compensation organizations. This study revealed three major findings. First, procedural justice, distributive justice, and interactional justice appeared to have positive effects on employee job satisfaction. Second, interactional justice appeared to have a positive effect on organizational commitment to employee invention compensation. Third, distributive justice and interactional justice in employee invention compensation have positive effects on organizational citizenship behavior. This study showed meaningful implications as follows. First, the study proved that not only ‘reasonable compensation’ but also ‘fair compensation’ should be applied to employee invention compensation. In order to encourage employees` volition and behavior to invent and to create superior inventions, employee invention compensation should be fair compensation. Second, in order to induce voluntary volition and behavior to contribute to his organization and job, the level of employee invention compensation should be ‘appropriate compensation’ to satisfy employee’s expectation.